Implementation of Academic Supervision in Elementary Schools - Kapoh, Defnny C.; Sumual, Tinneke E. M.; Sumual, Shelty D. M. (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This study aims to determine and analyze: (a) Academic Supervision Planning by the principal of Alexa Lotta Elementary School. (b) Implementation of academic supervision in the process at Alexa Lotta Elementary School. (c) Follow-up of Academic Supervision results at Alexa Lotta Elementary School. (d) Evaluation of Academic Supervision at Alexa Lotta Elementary School. The method used in this study is a descriptive qualitative research method. The data collection and recording procedures are carried out through the stages; (1) orientation stage, (2) exploration stage, (3) member check stage. The data collection techniques used are: observation, documentation and interviews. The main instrument in this study is the researcher himself who is equipped with interview guidelines, a camera, a mobile phone, and field notes. The data obtained are then read, studied, reviewed and analyzed then with the following steps: (1) data reduction, (2) data presentation, (3) drawing conclusions. Based on the results of data analysis, the following conclusions were obtained: (1) Supervision always begins with providing information to teachers and the Principal conveying the things to be supervised including supervision techniques (2) Supervision is carried out directly when teachers are teaching. In the implementation of supervision, the principal provides direction/input related to effective learning activities (3) and the principal evaluates whether the implementation of supervision is in accordance with the planning that has been prepared. (4) Follow-up to supervision activities where teachers always improve inappropriate teaching methods. Teachers are required to complete any deficiencies found during supervision such as administration in teaching and learning activities.